IMPLEMENTASI BUDAYA RELIGIUS DI SDN PAGENDINGAN 2 GALIS PAMEKASAN (STUDI KASUS DI SDN PAGENDINGAN 2 KECAMATAN GALIS KABUPATEN PAMEKASAN) - Faradila Aini; Sri Nurhayati (IAIN Madura, 2020)
ABSTRACTThere are two problems that become the main study in this study, namely first; What are the forms of religious culture in SDN Pagendingan 2 Galis Pamekasan ?, Second; What are the supporting and inhibiting factors for the implementation of religious culture in SDN Pagendingan 2 Galis Pamekasan. In this study, researchers used qualitative research methods, this type of research is descriptive. With the procedure of collecting data through interviews of the Principal and direct observations. While checking the validity of the data is done by extending the presence of researchers and triangulation. The results of this study are as follows: First; the forms of pesantrenan culture in SDN Pagendingan 2 Galis Pamekasan include the following: 1) dhuha prayer in congregation; 2) read juz amma before the lesson begins; 3) reading the prayer before the lesson; 4) tahfidz program; 5) Dhuhr prayer in congregation: 6) recite the prayer before going home from school; 7) carrying out santri day: 8) carrying out the Prophet's birthday: 9) reading the yasin and istighasah together every Friday sweet: 10) doing the ramadan hut; 11) compensation for orphans in Ashura, second; Supporting factors for the implementation of religious culture in SDN Pagendingan 2 Galis Pamekasan in implementing pesantrenan culture can be divided into three factors, namely: 1. Teacher factors,, 2. Student factors, and 3. Parent factors. While the inhibiting factors of the implementation of religious culture in SDN Pagendingan 2 Galis Pamekasan in the implementation of religious culture consists of two factors, namely: 1. Student factors, and 2. Parental factors. ABSTRAKAda tiga permasalahan yang menjadi kajian pokok dalam penelitian ini, yaitu pertama; Apa saja bentuk-bentuk budaya religius di SDN Pagendingan 2 Galis Pamekasan?, Kedua; Apa saja faktor pendukung dan penghambat implementasi budaya religius di SDN Pagendingan 2 Galis Pamekasan. Penelitian ini menggunakan metode penelitian kualitatif, jenis deskriptif. Dengan prosedur pengumpulan data melalui wawancara dan observasi langsung. Sedangkan pengecekan keabsahan data dilakukan melalui perpanjangan kehadiran peneliti dan triangulasi. Hasil dari penelitian ini adalah sebagai berikut: Pertama; bentuk-bentuk budaya kepesantrenan di SDN Pagendingan 2 Galis Pamekasan antara lain adalah sebagai berikut: 1) shalat dhuha berjama`ah; 2) membaca juz amma sebelum pelajaran dimulai; 3) membaca do`a sebelum pelajaran; 4) program tahfidz; 5) shalat dhuhur berjama`ah: 6) membaca do`a sebelum pulang sekolah; 7) melaksanakan hari santri: 8) melaksanakan maulid Nabi: 9) pembacaan surat yasin dan istighasah bersama setiap hari jum`at manis: 10) melakukan pondok ramadhan; 11) santunan anak yatim di bulan asyura., Kedua; faktor pendukung implementasi budaya religius di SDN Pagendingan 2 Galis Pamekasan dalam implementasi budaya kepesantrenan dapat dibedakan menjadi tiga faktor, yaitu: 1. Faktor guru, 2. Faktor siswa, dan 3. Faktor orang tua. Sedangkan faktor penghambat implementasi budaya religius di SDN Pagendingan 2 Galis Pamekasan dalam implementasi budaya religius terdiri dari dua faktor yaitu: 1. Faktor siswa, dan 2. Faktor orang tua.